The Effect of Emotional Intelligence and Work-Life Balance on Organizational Citizenship Behavior Mediated by Job Satisfaction in PT. PLN (Persero) UP2D South and Central Kalimantan, Indonesia - Mutamadra, Junan; Meiske Claudia (Open Access Indonesia Journal of Social Sciences, 2024)
Emotional intelligence and work-life balance are important factors that can influence employee organizational citizenship behavior (OCB). OCB refers to voluntary employee behavior that is not required in the job description but is beneficial to the organization. Job satisfaction is also believed to be a mediator that connects these variables. This research uses a quantitative design with survey methods. A total of 60 employees of PT. PLN (Persero) UP2D South and Central Kalimantan was the research respondent. Data was collected via a Likert questionnaire and analyzed using SmartPLS 3.0. The research results show that emotional intelligence has a significant positive effect on OCB. Work-life balance does not have a significant effect on OCB. Job satisfaction does not have a significant effect on OCB. Emotional intelligence has a significant positive effect on job satisfaction. Work-life balance does not have a significant effect on job satisfaction. Job satisfaction does not mediate the influence of emotional intelligence and work-life balance on OCB. In conclusion, emotional intelligence has a positive influence on OCB and job satisfaction, while work-life balance and job satisfaction do not show a significant influence. Job satisfaction was not proven to be a mediator in this study.